If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6=5/6(12-b)+1
We simplify the equation to the form, which is simple to understand
6=5/6(12-b)+1
Simplifying:
6=0.833333333333*(12-b)+1
Reorder the terms in parentheses
6=+(+10-0.833333333333b)+1
Remove unnecessary parentheses
+6=+10-0.833333333333b+1
We move all terms containing b to the left and all other terms to the right.
+ 0.833333333333b=+10+1-6
We simplify left and right side of the equation.
+ 0.833333333333b=+5
We divide both sides of the equation by 00.833333333333 to get b.
b=6
| 15+3(3u-1)=16-(3u-8) | | 1.7-.9-.4x=-.6 | | x^3-5x^2+6x-8= | | 243=9(9x) | | n(-3)=33 | | x-6/3=1 | | 12x^2-76x+78=0 | | 28=1.8(X)+32 | | 4x=52-(x-7) | | u(9)=6 | | 2e^7x=84 | | 5(h-1)=30 | | -16t^2+400t=0 | | m(7)=10 | | 48+25+x=4x | | -3.2x-1.68=-10.00 | | (x-7)/3=1 | | (12a+2)+9= | | 10x+50=9(x+7) | | 6x+7+3x=6+2*9 | | 3(2x-1)-x=-12 | | 4(169+31)+y=21y | | x(2x-11)=-12 | | 24x=8(x-4) | | -35=5n | | 82=(2)(3.14)(65)(L) | | -20(x-2)=-30x | | 4x-8=12x-48 | | 4-3p=13 | | 15=8+7x | | 6x-16=92 | | 3.5t+4.5t+7=2t-3 |